Understanding network emergence after turbulent industrial relocation: A Swedish biorefinery initiative. Issue 5 (October 2016) - Lundberg, Heléne; Andresen, Edith; Törnroos, Jan-Åke
Abstract: The paper examines network development and reconfiguration in the aftermath of industrial restructuring. The research combines a sensemaking approach with process research into business network development. A longitudinal case study examines a unique setting and critical change processes created by the restructuring of an old industrial site. Managers of businesses, previously belonging to a multinational company, initiated joint R&D in a networking context, putting their resources to novel use by creating a biorefinery initiative. Their previously intra-organizational relationships were turned into inter-organizational relationships and over time additional, and other types of actors joined the growing network. The individual actors are key drivers in the upcoming situation and their sensemaking and acts form key processual elements in sensemaking and network development. The study contributes to research on network reconfiguration and network orchestration. It has practical implications for managerial action in times of crisis and turbulence and for the role of individuals in creating novel business networks.